Increased frequency of linezolid resistance among clinical Enterococcus faecium isolates from German hospital patients - Klare, Ingo; Fleige, Carola; Geringer, Uta; Thürmer, Alexander; Bender, Jennifer; Mutters, Nico T.; Mischnik, Alexander; Werner, Guido (Journal of global antimicrobial resistance, 2015)
Linezolid is an antibiotic of last resort for the treatment of infections with vancomycin-resistant enterococci (VRE). Here we report the increasing prevalence of linezolid resistance among clinical Enterococcus faecium strains from German hospital patients.
Gesehen am 07.07.2020